Curricular internship in special education in initial teacher training in Physical Education. The case of a Brazilian public university - Munhoz Gomes, Nilton (2021)
This study aimed to analyze the perception of undergraduate students in Physical Education regarding the completion of the curricular internship in the area of Special Education considering their initial training process, as well as to identify the opinion of academics regarding a proposal different from the conventional internship. Search is descriptive. 75 undergraduate students in Physical Education participated. An instrument with eight statements with justification of the answer option was used. The results showed that no significant differences were observed between the control and experimental groups before the beginning of the internship. It was observed that the experimental group showed significant improvement in all questions, between pre and post intervention. It is concluded that the proposed internship brought academics a positive perception of its effectiveness in training teachers to work in the EE area.